2020
DOI: 10.1111/epi.16592
|View full text |Cite
|
Sign up to set email alerts
|

Functional and behavioral signatures of Kv7 activator drug subtypes

Abstract: Objective: Voltage-gated potassium channels of the KCNQ (Kv7) family are targeted by a variety of activator compounds with therapeutic potential for treatment of epilepsy. Exploration of this drug class has revealed a variety of effective compounds with diverse mechanisms. In this study, we aimed to clarify functional criteria for categorization of Kv7 activator compounds, and to compare the effects of prototypical drugs in a zebrafish larvae model. Methods: In vitro electrophysiological approaches with recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…In general, there seems to be a good correlation between neural activity measured by CaMPARI and locomotor activity 61 , 62 . However, some findings may be more sensitive towards one assay vs another, as described above.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In general, there seems to be a good correlation between neural activity measured by CaMPARI and locomotor activity 61 , 62 . However, some findings may be more sensitive towards one assay vs another, as described above.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we believe this method is a suitable technique to measure substantial changes in neural activity in the larger parts of the zebrafish CNS. For future studies in connection to epilepsy this innovation may be particularly helpful as some studies use convulstants, PTZ or 4-AP, to simulate seizures 62 , 65 . Indeed, we found that both, PTZ and 4-AP, induce CaMPARI activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects on motor axons will be detected by our behavioural assay. In general, there seems to be a good correlation between neural activity measured by CaMPARI and locomotor activity 61,62 . However, some findings may be more sensitive towards one assay vs the other, as described above.…”
Section: Discussionmentioning
confidence: 94%
“…We believe this method is a suitable technique to measure substantial changes in neural activity in the larger parts of the zebrafish CNS. For future studies in connection to epilepsy this innovation may be particularly helpful as some studies use convulstants, PTZ or 4-AP, to simulate seizure 62,65 . We found that both, PTZ and 4-AP, induce CaMPARI activity.…”
Section: Discussionmentioning
confidence: 99%